METODE EKLEKTIK DALAM PEMBELAJARAN BAHASA ARAB - Azizul Hakim (Transformasi : Jurnal Kepemimpinan & Pendidikan Islam, 2021)
This paper discusses the basic teaching principles by examining the development of Arabic teaching methods and systems. Each method has its strengths and weaknesses. Based on this fact, the mixed method implies selection and amalgamation. However, the merger is not meant to combine all existing methods at once but to take advantage of the advantages of certain methods. In this paper, the author discusses mixed methods in learning Arabic. Knowing this material is especially important for Arabic language teachers or lecturers to streamline the teaching and learning process by using the most suitable methods for various purposes. The main problem that the author discusses in this paper is the background and basic concepts of the mixed method, the steps for its use, and its advantages and disadvantages. This paper concludes that the mixed method is a language teaching method that combines several methods. The mixed-method does not have a special form that is completely different from other methods because it is the result of selecting and combining several methods that are considered relevant for learning. The advantages of the mixed method are more varied learning activities and the ability of students to use foreign languages ​​more evenly. The drawback is that using the mixed method will have problems with the willingness of teachers and students and the allocation of time.